Problems of Realization of the Sovereignty of the Institute "Habeas Corpus Act" in the Criminal Procedure - Bozorov Maqsudali Maxmudovich; Abdiaxatov temur Rovshan o’g’li (Periodica Journal, 2022)
This article discusses the institution of habeas corpus, its concept, content, history of origin and development, the role of habeas corpus intitu in criminal proceedings, as well as the issues of improving the application of the institution of habeas corpus to improve criminal procedure law, reforms to improve the sector, suggestions and recommendations to address their problems and shortcomings.
Keywords: corpus; habeas corpus ad subjiciendum; criminal proceedings; precautionary measure